Comparing long‐term outcomes of primary and progressive carcinoma invading bladder muscle after radical cystectomy. (3rd June 2015) - Moschini, Marco; Sharma, Vidit; Dell'oglio, Paolo; Cucchiara, Vito; Gandaglia, Giorgio; Cantiello, Francesco; Zattoni, Fabio; Pellucchi, Federico; Briganti, Alberto; Damiano, Rocco; Montorsi, Francesco; Salonia, Andrea; et al.
Abstract : Objective: To assess the impact of primary or progressive status on recurrence‐free survival (RFS), cancer‐specific mortality (CSM) and overall mortality (OM) after radical cystectomy (RC) for muscle‐ invasive bladder cancer (MIBC). Patients and Methods: A total of 768 consecutive patients underwent RC as treatment for MIBC at our institution between 2000 and 2012. Primary MIBC was defined as no previous history of bladder cancer and progressive was defined as recorded previous treated non‐MIBC (NMIBC) that had progressed to MIBC. The median follow‐up was 85 (60–109) months. Univariate and multivariate Cox regression models were used to compare RFS, CSM and OM between these two cohorts. Results: In all, 475 (61.8%) patients had primary and 293 (38.2%) patients had progressive MIBC. There were no differences between the two groups in terms of demographics, pathological and peri‐operative complications (all P > 0.1). The 10‐year RFS, CSM and OM rates for primary vs progressive status were 43 vs 36% ( P = 0.01), 43 vs 37% ( P = 0.01), and 35 vs 28% ( P = 0.03), respectively. On multivariable Cox regression analyses, progressive status remained significantly associated with a higher rate of recurrence (hazard ratio [HR] 1.47, 95% confidence interval [CI] 1.12–1.79; P = 0.03), CSM (HR 1.42, 95% CI 1.07–1.89; P = 0.01) and OM (HR1.42, 95% CI 1.13–1.65; P = 0.02). Conclusions: Among patients treated with RC for MIBC, progressive status was associated with a higher CSM, OM and recurrence rate after RC. The present study thus provides an impetus to improve risk sub‐stratification when bladder cancer is still at the NMIBC stage, be it through new biomarkers or improved imaging, as a subset of patients with NMIBC are likely to benefit from early RC.